Lithological and Morphological Characteristics and Rock Relief of the Lao Hei Gin Shilin-Stone Forest (Lunan, SW China) - Martin Knez; Tadej Slabe (Acta Carsologica, 2006)
The Lao Hei Gin stone forest is yet one more of the diverse and famed Lunan stone forests created from subcutaneous karren. The initial morphogenesis of the stone pillars started along almost horizontal bedding planes and mostly sub-vertical faults and cracks already covered by thick layers of sediments and soil. The forest’s stone pillars stand individually or in groups. The dominant and most characteristic shape of the pillars is mushroom-like, with alternating lithological characteristics of the carbonate beds expressed in a vertical direction.